"Superstition Remains at This Hour": The Friers Chronicle (1623) and England's Long Reformation. Issue 2 (3rd July 2019) - Lyon, Harriet
ABSTRACT: This article examines an unusual piece of Reformation polemic, T. G.'s The friers chronicle (1623), with a view to shedding fresh light on the long literary afterlives of the dissolution of the monasteries (1536–40). Previous accounts have focussed on ruins as emblems of the rupture between past and present engendered by the dissolution. However, The friers chronicle suggests that the memory of the monasteries also resonated powerfully with Protestant anxieties about the future of the ongoing Reformation in the late sixteenth and seventeenth centuries, especially at moments of renewed anti-Catholic crisis. In turn, the dissolution itself contributed to a "long reformation" of the chronicle genre. In this way, the paradigm of the long Reformation has the potential to illuminate the impact of the dissolution upon English literature, as well as highlighting the importance of literary sources for understanding its legacies and afterlives.